H Impact of Instructor Versus Student Facilitator Debriefing Following Clinical Simulation Sessions on Nursing students’ Self-Efficacy, Satisfaction, and Achievement - Helal, Houaida; Hafez, Samar (International Journal For Research In Health Sciences And Nursing, 2019)
Debriefing is an effective educational tool commonly used with adult learning following simulated session. A comparative interventional design was utilized to compare the impact of instructor versus student facilitator debriefing following clinical simulation sessions on nursing students’ self-efficacy, satisfaction, and achievement. A convenience sample of 151 nursing students enrolled in community nursing and obstetrics and gynecological nursing courses according to the curriculum plan in the Faculty of Nursing at Alexandria University, Egypt participated in the study. Students went through a debriefing process by both instructor and students during two simulation sessions. General perceived self-efficacy scale, satisfaction with simulation experience scale and students’ achievement records were used for data collection. Results revealed no statistically significant difference between the effect of debriefing done by instructors or students on their perceived self-efficacy, satisfaction with simulation experience and their clinical performance among neither obstetrics nor community nursing groups during first as well as second simulation sessions. The study concluded that the role of both instructor and student facilitator should be considered in a debriefing following nursing simulation experience and their active contribution to the learning process. Further researches are recommended to investigate the potential for using the self-debriefing method to enhance the efficiency of simulation-based education.